ANALISA SISTEM INFORMASI KEAMANAN INTERNET SPEEDY PADA PLASA TELKOM TANJUNGBALAI - Khairul Saleh; Tini Fitriani (Universitas Asahan, 2017)
Abstrack - The application of information technology at this time is very closely related to everyday life. Komunikas which at first was only conveyed in a very simple way, namely